Persekongkolan Pelaku Usaha Dalam Kegiatan Tender Pengadaan Alat-Alat Kedokteran Rsud Abdoel Wahab Sjahranie Samarinda (studi putusan kppu perkara nomor: 24/kppu-i/2016) - Novia Amelia Putri; Ali Mansur; Fitriyani Zein (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis study aims to determine violations committed by business actors in the tender for procurement of medical devices carried out by Abdoel Wahab Sjahranie Hospital Samarinda and the Commission Council consideration in Case Decision Number: 24 / KPPU-I / 2016. There are allegations of unfair business competition practices by several business actors in participating in the tender. Alleged violations of Article 22 of Law Number 5 of 1999 Concerning Prohibition of Monopolistic Practices and Unfair Business Competition, because in participating in the tender package several business actors formed teams on each package with the aim of fulfilling the requirements stipulated in Presidential Regulation Number 54 of 2010 concerning Government Goods / Services Procurement as per the new rules of Presidential Regulation Number 16 of 2018. This research uses qualitative research and normative research approaches using statutory legal materials, books or research-related literature, articles in legal-related research journals, and article on the internet. The results of the study showed that business actors were indicated to commit acts that prevented other business actors from competing fraudulently by creating artificial competition when participating in tender activities in violation of Article 22 of Law Number 5 Year 1999.Keywords: Conspiracy, Tender, Procurement, Affiliation, KPPU